Peningkatan Minat Wirausaha Siswa Melalui Layanan Dasar Bidang Bimbingan Karir - Monica Ivana Putri; Wedra Aprison; Fadhilla Yusri (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah dan Komunikasi, 2021)
The purpose of this study is that researchers want to see how much an increase in student entrepreneurial interest in SMK 1 Kec. Guguak through basic services in the field of career guidance. The population is all grade XII students of SMKN 1 Kec. Guguak, amounting to 236 people, while the research sample were students of class XII multimedia 2, amounting to 20 people. Which is indicated to have low student entrepreneurial interest based on a purposive sampling technique. The data collection instrument is a Likert scale. Data analysis techniques using, normality test, homogeneity test, and hypothesis testing using Statistical Product and Service Solution (SPSS) version 22. The results of research that have been done there are differences between the pretest value and the posttest value. From the results of statistical tests it is known that tcount 4,737> from ttable 1,729 with df 19 at a significance level of 0.05, it can be said that Ha is accepted meaning that there is an increase in student entrepreneurial interest for pretest and posttest through basic services in career guidance.